Pertumbuhan Fase Bahan Superkonduktor Bi-2223 dengan Variasi Doping Pb (BPSCCO-2223) pada Kadar Ca=2,10 dan Suhu Sintering 855oC - suprihatin suprihatin (Jurnal Teori dan Aplikasi Fisika, 2016)
Abstract. The synthesis of BSCCO-2223 superconducting material with varians of doping Pb (BPSCCO-2223) at level of Ca = 2,10 and sintering temperature of 855oC has been done by solid state reaction method. The varians of doping Pb was used for the research are 0,00; 0,01; 0,20; 0,30; and 0,40. Variation was carried out to determine the effect of doping Pb on phase formation superconducting material of BPSCCO-2223 that views based on volume fraction, the degree of orientation and impurities. Calcination was executed for 10 hours at temperature of 800oC and sintering for 20 hours at temperature of 855oC. Result of research shows the increase of doping Pb in the sample could increase volume fraction of BPSCCO-2223 and decrease impurity. Volume fraction value of BPSCCO-2223 that is relatively high is 62,06% on doping Pb 0,40. The lowest volume fraction is 42,14% on doping Pb 0,00. The degree of orientation in the sample without doping Pb is 38.51%, the value of degrees of orientation decreases in the sample with doping Pb 0.10 to 21.81%. Then the degree of orientation will increase along with the increase of doping Pb (0.01-0.04). The degree of orientation in sample of doping Pb 0.40 is 38.13%. Besides the addition of doping Pb will decrease the value of impurities. The lowest impurity value of is 37,94% on doping Pb 0,40. Result of SEM shows that all samples have shown that layers arranged in the direction of the empty space between the plates (void) is relatively small.